ILRI's goal and strategic research themes. Revised strategy for 2002-2007 - Seré Rabé, Carlos (International Livestock Research Institute, 2003)
This Report illustrates the importance and the contribution of the livestock sector in African rural Development. It presents ILRI's strategic goals and research themes in the context of improving the livelihood and social well-being of the poor through managing and mitigating risk and vulnerability.